How Regional Income Affects Poverty Reduction: A Study of Central Java (2017-2020) - Yusuf, Maulana Ghani; Pratysto, Tangguh (Transpublika Publisher, 2025)
Poverty remains one of the most pressing development challenges in Central Java, where regional disparities and limited fiscal capacity continue to hinder the effectiveness of poverty alleviation programs. Despite substantial transfers from the central government, inefficiencies in fund allocation combined with low fiscal independence at the local level have slowed progress in reducing poverty. This study examines the impact of regional fiscal instruments and macroeconomic factors on poverty levels across 34 districts and cities in Central Java from 2017 to 2020. Using panel data and the Feasible Generalized Least Squares (FGLS) method, supported by diagnostic tests to ensure the model meets the BLUE (Best Linear Unbiased Estimator) criteria. The findings reveal that Regional Original Income (PAD), Other Legitimate Income, and Gross Regional Domestic Product (GRDP) per capita play a role in reducing poverty, although the effects of PAD and Other Legitimate Income are only marginally significant. By contrast, Balancing Funds from the central government are positively and significantly associated with higher poverty rates, suggesting inefficiencies in their distribution and utilization. The Open Unemployment Rate is found to have no significant effect on poverty during the study period. Taken together, these results underscore the importance of strengthening local fiscal capacity, enhancing the efficiency of central government transfers, and promoting inclusive economic growth as integral components of long-term poverty reduction strategies in the region.